Fascial preadipocytes: another missing piece of the puzzle to understand fibromyalgia? - Bordoni B (Dove Medical Press, 2018)
Bruno Bordoni,1 Fabiola Marelli,2,3 Bruno Morabito,2–4 Francesca Cavallaro,5 David Lintonbon6 1Foundation Don Carlo Gnocchi IRCCS, Department of Cardiology, Institute of Hospitalization and Care with Scientific, Milan, Italy; 2CRESO, School of Osteopathic Center for Research and Studies, Department of Fascial Osteopathic Research: FORe, Gorla Minore, Italy; 3CRESO, School of Osteopathic Center for Research and Studies, Department of Fascial Osteopathic Research, Fano, Italy; 4Sapienza University of Rome, Department of Radiological, Oncological and Anatomopathological Sciences, Rome, Italy; 5ICOM, International College of Osteopathic Medicine, Torino, Italy; 6London School of Osteopathy, Department of Osteopathic Technique, London, UK Abstract: Fibromyalgia (FM) syndrome is a chronic condition causing pain, affecting approximately 0.5%–6% of the developed countries’ population, and on average, 2% of the worldwide population. Despite the large amount of scientific literature available, the FM etiology is still uncertain. The diagnosis is based on the clinical presentation and the severity of the symptomatology. Several studies pointed out pathological alterations within the central nervous system, suggesting that FM could originate from a central sensitization of the pain processing centers. Research supports the thesis of a peripheral neuropathic component, with the finding of axonal damages. The fibromyalgia patient has many myofascial system abnormalities, such as pain and fatigue, impairing the symptomatic profile. This paper revises the myopathic compensations, highlighting the possible role of the fascia in generating symptoms, being aware of the new information about the fascia’s activity in stimulating inflammation and fat cell production. Keywords: fibromyalgia, fascia, pain, myofascial, neuropathic pain